The Usage of Inferential Statistics in Stylistics (Case Study: the Literal Similes in Sixth Century) - Morteza Heidary (Matn/Pizhūhī-i Adabī, 2015)
The stylistics deals with studying frequencies and repetitions. Therefore, the employing of statistical analyses in stylistic evaluations is very useful. Since descriptive statistics do not always explain stylistic fluctuations, using of inferential statistics methods in evaluating stylistic, have very high scientific accuracy in assessing of stylistics phenomena.Stylometry is coined for stylistic researches related to the computer. In this article,itis evaluated the relationship between compression angle of simile constructionin thesixthcenturypoetry and frequency of construction of literal similes in the poets’ divan of this century and in passing of the time. Thus, wediscussstatistical inferenceanalysisby using thePearson correlation coefficient in SPSS computerized software. Direct and positive relationship between variables is confirmed according to quantitative resultsderived from thespss softwarewhich indicates the correlation coefficient and significance level of the relationship betweenvariables (the compression of simile angle and frequency of literal similes) and comparingthenumberswithdefinedparametersforcorrelation coefficientanda significantlevel.In stylisticlanguage, beingmore compact of simile angle in the poetry of the sixth century means increasing of the frequency in the literal similes with a more closed constructionand this stylistic event has followed the dominant norms on periodic style.